Effects of feeding frequency on the survival, growth and body composition of buffalo leech, Hirudinaria manillensis - Teh, Jun Chin; Kamarudin, Mohd Salleh; Abd Rahim, Abdullah; Saad, Che Roos; Fard, Ehsan Ramezani (Academic Journals, 2013)
The growth and survival of leeches are highly affected by environmental changes particularly the availability of food. In this study, Asian buffalo leeches Hirudinaria manillensis were stocked in 10 L aquaria at 10 leeches per aquarium and randomly assigned to five different feeding frequencies (once every 3, 6, 12 and 24 days) and no feeding. The leeches were fed with prewarmed cattle blood in rubber sacs. The results showed that leech fed every 3 days had the highest average growth both by day 30 (82.8%) and day 60 (115.8%). This followed by those fed every 6, 12 and 24 days. By day 60, no significant differences in growth were found among the feeding leeches except those fed at every 24 days which have a significantly much lower growth. Starved leeches (FS) had a negative growth throughout the experiment. The weight lost in starved leeches was due to the depletion of reserved energy in the body. The protein content of all leeches was extremely high (about 80%) and no significant differences in the body composition of among treatments were found. The study also showed that leech survival was not significantly affected by feeding frequency. A feeding interval of 6-12 days was recommended for the commercial culture of leech H. manillensis.